INSECTICIDAL AND REPELLENT ACTIVITIES OF CITRUSSINENSIS (L.) LEAF EXTRACT AGAINST TROGODERMA GRANARIUM EVERTS (COLEOPTERA: DERMASTIDAE IN STORED GROUNDNUT (FUDMA JOURNAL OF SCIENCES, 2021)
Groundnut production has been reported to be threatened by storage insect pests which caused significant damage in storage. The repellent and efficacy activities of Citrus sinensis leaf extract were assessed on Trogoderma granarium in stored groundnut. The treatment was laid in a Completely Randomized Design with 3, 5, and 7% concentration level of methanolic and petroleum ether Extract for insecticidal activities. The results of C. sinensis leaf extract toxicity obtained was significant at 7% concentration at 24, 48 and 72 hours after treatment with 100% and 80% mortality in methanolic and Pet. ether extracts respectively in adults. Half disc experiment was carried out to determine the repellency activities with 1, 2, and 3% concentration of methanolic and pet. ether extract. It was observed that at 2HAT the insects moved towards the extract with the Index of Repellency of 1.13 at 3 % concentration for methanolic and pet ether extract, as the hours increase from 4 to 6HAT it was observed that the extract acted as repellant towards the insect with methanol and petroleum ether extract of 3 % concentration having the highest repellency index of 0.47. Petroleum ether at 1 % concentration with the value of 1.47, 1.40 and 1.20 repellency index across the 2, 4 and 6HAT showed that the extract remains an attractant towards T. granarium. The results obtained from this study is an indication of the potential of methanolic and petroleum ether crude extract of C. sinensis in groundnut storage
Keywords: Repellency, T. granarium, C. sinensis, Petroleum ether, Repellency index